Biomimetic reduction of imines and heteroaromatics with chiral and regenerable [2.2]Paracyclophane-Based NAD(P)H model CYNAM. (12th March 2021) - Zhu, Zhou-Hao; Ding, Yi-Xuan; Zhou, Yong-Gui
Abstract: In our previous work, we reported the synthesis of chiral and regenerable [2.2]paracyclophane-derived NAD(P)H models CYNAMs and their application in biomimetic asymmetric reduction of tetrasubstituted olefins. Herein, the biomimetic asymmetric reduction of imines and heteroaromatics has been successfully achieved using the chiral and regenerable CYNAMs and simple achiral phosphoric acid as the transfer catalyst, providing the chiral amines with up to 99% yield and 99% ee. Graphical abstract: Image 1